On the Allocation of Time - A Quantitative Analysis of the U.S. and France - Georg Duernecker; Berthold Herrendorf (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study the allocation of time in the U.S. and in Europe during 1960–2010. We find that market hours decreased and leisure increased most in France and least in the U.S. Contrary to what standard theory predicts, home hours changed comparatively little. We show that the growth model with home production can account for the patterns in France and the U.S. if we feed in taxes and labor productivities. To obtain this result it is crucial to measure the labor productivity of home production in a comparable way in both countries, instead of calibrating these productivities like the literature does.
Keywords: E10; J40; 330; home production; labor productivity; leisure; time allocation